2013
DOI: 10.1093/infdis/jit038
|View full text |Cite
|
Sign up to set email alerts
|

Viral Shedding and Immune Responses to Respiratory Syncytial Virus Infection in Older Adults

Abstract: Multiple factors, but not older age, are independently associated with severe RSV infection in adults. The presence of underlying medical conditions had the greatest influence on disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 36 publications
5
89
2
Order By: Relevance
“…This is a general finding in cotton rats (15,17) and has also been described in humans (31). Observed differences in viral loads between nose and lungs might partly be due to differences between sampling methods.…”
Section: Fig 3 Rhrsv Vaccine-induced Serum Igg Cotton Rats At the Agsupporting
confidence: 71%
See 2 more Smart Citations
“…This is a general finding in cotton rats (15,17) and has also been described in humans (31). Observed differences in viral loads between nose and lungs might partly be due to differences between sampling methods.…”
Section: Fig 3 Rhrsv Vaccine-induced Serum Igg Cotton Rats At the Agsupporting
confidence: 71%
“…Since rHRSV is a live virus (17), rHRSV immunization can be regarded as a mild HRSV infection, and challenge with wtHRSV can be regarded as a boosting reinfection. A booster effect in previously immunized individuals becomes apparent by the quick and steep increase of the antibody titer during the recall immune response to infection within 5 to 7 days, as shown in our cotton rat studies (our unpublished data), lambs (42), young children (43), and aged humans (31). The early booster effect was significantly lower in old animals, and this was most pronounced for the increase in the level of neutralizing antibodies, rather than the boost of IgG, indicating that aged individuals are less capable of mounting recall responses of functional antibodies to HRSV.…”
Section: Fig 3 Rhrsv Vaccine-induced Serum Igg Cotton Rats At the Agsupporting
confidence: 59%
See 1 more Smart Citation
“…In a human challenge model using healthy adult volunteers, RSV nasal viral load is closely correlated with clinical symptoms and recovery [18]. Observational studies have shown that RSV viral load is higher and viral shedding more protracted in hospitalised adults compared to outpatients [19], and that a high viral load in hospitalised adults is a risk factor for the development of complications including respiratory failure and the need for mechanical ventilation [20,21]. In human challenge models of asthma and COPD exacerbation, using challenge with rhinovirus, viral load measured in sputum correlates with the degree of host inflammatory response [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in BALB/c mice have demonstrated that although both CD4 and CD8 T cells mediate viral clearance, CD4 and CD8 T cells also contribute to RSVassociated disease (8). Furthermore, several human studies have demonstrated that the increased presence of T cells is correlated to severe RSV disease in both children and the elderly (9)(10)(11)(12).…”
mentioning
confidence: 99%